New ideas for teaching electrocardiogram interpretation and improving classroom teaching content - Zeng, Rui; Yue, Rong-zheng; Tan, Chun-yu; Wang, Qin; Kuang, Pu; Tian, Pan-wen; Zuo, Chuan (Advances in medical education and practice, 2015)
Interpreting an electrocardiogram (ECG) is not only one of the most important parts of diagnostics but also one of the most difficult areas to teach. Owing to the abstract nature of the basic theoretical knowledge of the ECG, its scattered characteristics, and tedious and difficult-to-remember subject matter, teaching how to interpret ECGs is as difficult for teachers to teach as it is for students to learn. In order to enable medical students to master basic knowledge of ECG interpretation skills in a limited teaching time, we modified the content used for traditional ECG teaching and now propose a new ECG teaching method called the "graphics-sequence memory method." A prospective randomized controlled study was designed to measure the actual effectiveness of ECG learning by students. Two hundred students were randomly placed under a traditional teaching group and an innovative teaching group, with 100 participants in each group. The teachers in the traditional teaching group utilized the traditional teaching outline, whereas the teachers in the innovative teaching group received training in line with the proposed teaching method and syllabus. All the students took an examination in the final semester by analyzing 20 ECGs from real clinical cases and submitted their ECG reports. The average ECG reading time was 32 minutes for the traditional teaching group and 18 minutes for the innovative teaching group. The average ECG accuracy results were 43% for the traditional teaching group and 77% for the innovative teaching group. Learning to accurately interpret ECGs is an important skill in the cardiac discipline, but the ECG's mechanisms are intricate and the content is scattered. Textbooks tend to make the students feel confused owing to the restrictions of the length and the format of the syllabi, apart from many other limitations. The graphics-sequence memory method was found to be a useful method for ECG teaching.